International conflict management [ - Butler, Michael J. , 1972- (Abingdon, Oxon, UK. : Routledge, 2009)
Presents an overview of the logic, evolution, application and outcomes of the 5 major approaches of international conflict management: traditional peacekeeping; peace enforcement and support operations; negotiation and bargaining; mediation; and, adjudication. This book provides an understanding of the strengths and weaknesses of these techniques.
1. What is international conflict management? -- 2. The changing nature of security -- 3. The challenges of 'new wars' --Peacekeeping --A study in peacekeeping : UNOMIG in Georgia -- 4. Mediation -- 5. A study in mediation : IGAD in Sudan -- 6. Peace enforcement -- 7. A study in peace enforcement : INTERFET in East Timor -- 8. International adjudication -- 9. A study in international adjudication : the Mapiripan massacre.
Description based on print version record
Title from e-book title screen (viewed Sept 29, 2009)
Includes bibliographical references and index
Keywords: Conflict management; Peace-building; Peacekeeping forces; War -- Prevention